2021
DOI: 10.1111/cns.13731
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Double‐blind, randomized, placebo‐controlled pilot study of the phosphodiesterase‐3 inhibitor cilostazol as an adjunctive to antidepressants in patients with major depressive disorder

Abstract: Aims: Cilostazol (CLS) has shown antidepressant effect in cardiovascular patients, post-stroke depression, and animal models through its neurotrophic and antiinflammatory activities. Consequently, we aimed to investigate its safety and efficacy in patients with MDD by conducting double-blind, randomized, placebo-controlled pilot study. Methods: 80 participants with MDD (DSM-IV criteria) and Hamilton DepressionRating Scale (HDRS) score >20 were treated with CLS 50 mg or placebo twice daily plus escitalopram (ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 52 publications
(150 reference statements)
2
19
0
Order By: Relevance
“…According to the research of Khadivi et al., the HAMD score decreased significantly more in MDD patients treated with cilostazol and sertraline for six weeks than in those treated with sertraline alone, and the safety was no difference ( 89 ). When Cilostazol combined with escitalopram, similar results were obtained ( 90 ). A case report found that cilostazol was used intensively to treat a patient with intractable depression complicated by WMH.…”
Section: Potential Therapiessupporting
confidence: 65%
“…According to the research of Khadivi et al., the HAMD score decreased significantly more in MDD patients treated with cilostazol and sertraline for six weeks than in those treated with sertraline alone, and the safety was no difference ( 89 ). When Cilostazol combined with escitalopram, similar results were obtained ( 90 ). A case report found that cilostazol was used intensively to treat a patient with intractable depression complicated by WMH.…”
Section: Potential Therapiessupporting
confidence: 65%
“…Moreover, all of the side effects showed a mild, transient nature without needing urgent medical attention. These findings were in line with those reported in other trials of cilostazol add-on therapies in schizophrenia and major depressive disorder settings (Rezaei et al , 2017; Abdallah et al , 2021). Furthermore, as mentioned previously, cilostazol is primarily prescribed for its antiplatelet and vasodilation effects to improve claudication.…”
Section: Discussionsupporting
confidence: 92%
“…Beneficial therapeutic outcomes of cilostazol adjuvant therapy have been reported for schizophrenia (Rezaei et al , 2017), major depressive disorder (Abdallah et al , 2021), and Alzheimer’s disease (Tai et al , 2017). However, studying cilostazol application in ASD management has been limited to a single animal study.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that brain injury during stroke stimulates the body to produce a rapid immune regulatory response. The peripheral immune system recruits inflammation-related cells and develops inflammation-related factors, which migrate to the brain injury area through the damaged blood-brain barrier for immune regulation [72][73][74][75]. The imbalance of homeostasis in the inflammatory state alters the endocrine function of nerve cells.…”
mentioning
confidence: 99%